Skeletal Muscle Expression of Actinin-3 (ACTN3) in Relation to Feed Efficiency Phenotype of F2Bos indicus - Bos taurus Steers - Vaughn, Robert N.; Kochan, Kelli J.; Torres, Aline K.; Du, Min; Riley, David G.; Gill, Clare A.; Herring, Andy D.; Sanders, James O.; Riggs, Penny K. (Frontiers in Genetics, 2022)
In this study, gene expression networks were examined to identify genetic factors that influence feed efficiency in Bos indicus x Bos taurus steers. A measure of relative feed efficiency based on residual feed intake relative to predictions from the NRC beef cattle model was analyzed by use of a mixed linear model that included sire and family nested within sire as fixed effects, and age, animal type, sex, condition, and breed as random effects for 173 F2 Nellore-Angus steers. Based on these residual intake observations, individuals were ranked from most efficient to least efficient. Skeletal muscle samples were analyzed from 54 steers in 3 groups of 18 (high efficiency, low efficiency, and a statistically average group). For this study, a microarray analysis was conducted with RNA extracted from muscle samples from a subset of steers from each of these 3 efficiency groups. From microarray results, actinin3 (ACTN3), a muscle-specific structural protein, was selected for quantitative reverse transcriptase PCR analysis. Actinin-3 expression in skeletal muscle was 1.6-fold greater in inefficient steer group than in the efficient group (P=0.007). In addition to expression measurements, blocks of SNP haplotypes were assessed for breed or parent of origin effects. A maternal effect was observed for ACTN3 inheritance, indicating that a maternal B.indicus block conferred improved residual feed efficiency relative to the B.taurus copy (P=0.03). SNP haplotype analysis was conducted for m-calpain (CAPN2) and fibronectin1 (FN1), and a significant breed effect was observed for both genes, with B. indicus, and B.taurus alleles each conferring favorable efficiency when inherited maternally (P = 0.03 and P = 0.04). Because ACTN3 structural protein is specific to fast twitch (Type II) muscle fibers, and not present in slow twitch muscle fibers (Type I), muscle samples used for expression analysis were also assayed for fiber type ratio (Type II/Type I). Inefficient animals had fast fiber type ratio 1.8-fold greater than efficient animals (P=0.027). Since these fiber-types exhibit different metabolic profiles, we hypothesize that animals with greater fast twitch muscle fiber type proportion, as measured by ACTN3 expression, are less efficient than animals that have reduced proportion of fast twitch fibers.